Penghitungan Pemotongan Pajak Penghasilan Pasal 21 Atas Uang Lembur - Widjaja, Siana M. (Pelita Harapan University, 2005)
According to Tax Law No. KEP - 545/PJ/2000, overtime pay earned by an employee is classified as regular income such as salaries, wages, monthly pension, honorarium, allowances, and insurance paid by employer, so that income tax deduction on overtime pay is computed by added the overtime pay to the monthly salary. But an example of the computation has never been demonstrated by tax governor. According to the author, overtime pay cannot be classified as regular income as it happens irregularly and is irregular also in amount. To determine the right way to compute the income tax deduction on overtime pay is the objective of this article. Conclusion is taken after presenting various simulations of computation in several tables.